Pembuatan Sabun Padat Berbahan Minyak Atsiri Skala Rumah Tangga - Bening Kusumawati; Dita Atasa (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Making this soap aims to provide an explanation for making solid soap made from lemon essential oil as an effort to improve community skills and can be applied by the community in the future as a business. Soap making is done by heating coconut oil at a temperature of 800C. Mix 30% NaOH with heated oil until it becomes homogeneous, stirring continuously until the saponification process is perfect. Add the stearic acid which has been dissolved in the alcohol and stir until smooth, add the white sugar and stir again, add the glycerin while stirring, add the foam booster while continuing to stir until the mixture becomes homogeneous. Add coloring and fragrance, namely lemon oil, which is carried out at 400C. Pour the mixture into the mold and let it sit for 15-30 minutes. The soap has hardened and can be removed from the mold. The tests performed were preference, allergy, aroma, color, froth and density tests. The result shows that solid soap has been successfully made, but still requires some further refinement regarding the density and transparency of the soap. With the procedures for making soap and the analytical test that the author described above, new knowledge and skills can be used for the community as well as solid soap business opportunities